Neuronal-glial anatomical plasticity in the hypothalamus - Oliet, Stéphane H.R. (Henry Stewart Talks, 2013)
Anatomical remodelling of the hypothalamo-neurohypophysial system during specific physiological conditions, Charactersiation of this remodelling by reduction in the astrocytic coverage of manocellular neurons and their synapses, Electrophysiological approaches show changes in the glial environment of neurons and synapses can dramatically alter synaptic functions, The hypothalamo-neurohypophysial system as an experimental model to study the contribution of astrocytes to synaptic transmission and plasticity